Exploring Pathways for Integrating Digital Economy with Traditional Industries: A Strategic Approach to Development and Growth (BIMA Journal (Business, Management, & Accounting Journal), 2024)
목적: 이 논문은 디지털 기술을 기존 산업에 통합하기 위한 전략적 경로를 탐구하고, 디지털 경제의 혁신적 잠재력을 강조합니다. 방법론: 포괄적인 분석 방법을 사용하여 이 연구는 기술 도입 및 스마트 업그레이드, 프로세스 최적화 및 디지털 통합, 조직 재구조화 및 민첩성, 문화적 변화 및 디지털 사고방식, 전략적 파트너십 및 생태계 협업의 5가지 중요한 경로를 식별합니다. 결과: 기술 도입을 전략적 조직 및 문화적 변화와 일치시키는 것이 성공적인 디지털 혁신을 달성하는 데 필수적임을 보여줍니다. 결과: 이러한 경로가 어떻게 운영 효율성을 향상시키고, 혁신을 촉진하고, 역동적인 시장에서 경쟁 우위를 유지하는지 강조합니다. 참신성: 참신성은 기술, 조직 및 문화적 차원을 결합하여 디지털 혁신 과제를 해결하는 전체적인 접근 방식에 있습니다. 독창성: 산업이 지속 가능한 개발을 위해 디지털 경제를 활용할 수 있는 통합 로드맵을 제공하는 데 있습니다. 결론: 전체적인 접근 방식을 채택하면 성장과 장기적 경쟁력이 보장됩니다. 논문 유형: 전략적 개념 논문 Purpose: This paper aims to explore strategic pathways for integrating digital technologies into traditional industries, emphasizing the transformative potential of the digital economy. Methodology: Using a comprehensive analysis method, the study identifies five critical pathways: technological adoption and smart upgrades, process optimization and digital integration, organizational restructuring and agility, cultural transformation and digital mindset, and strategic partnerships and ecosystem collaboration. Results: Demonstrate that aligning technology adoption with strategic organizational and cultural shifts is essential for achieving successful digital transformation.Findings: Highlight how these pathways enhance operational efficiency, foster innovation, and sustain competitive advantage in dynamic markets.  Novelty: The novelty lies in its holistic approach, combining technological, organizational, and cultural dimensions to address digital transformation challenges. Originality: Lies in offering an integrated roadmap for industries to leverage the digital economy for sustainable development.  Conclusion: adopting a holistic approach ensures growth and long-term competitiveness. Type of paper : Strategic Conseptual Paper